STRATEGIC HUMAN RESOURCE OPTIMIZATION IN BUSINESSMANAGEMENT AMIDST THE TECHNOLOGICAL EPOCH FOR ADVANCING PROFITABILITY AND SUSTAINABILITY IN INDONESIA - Albert Budiyanto; A. Hamid; Muhammad Syafri; A. Haris Mzen; Mohammad Aldrin Akbar (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In the study "Strategic Human Resource Optimization in Business Management Amidst the Technological Epoch for Advancing Profitability and Sustainability in Indonesia," we investigated the dynamic interplay between human resource strategies, technological advancements, and their impact on business profitability and sustainability in the Indonesian context. Our research employed a mixed- method approach, incorporating quantitative and qualitative data collection techniques. We analyzed extensive data from various Indonesian businesses spanning multiple sectors and industries. These data were meticulously gathered and processed, utilizing advanced statistical tools and software to derive meaningful insights. The study's results indicated a compelling relationship between the optimization of human resources, driven by strategic initiatives, and the ability of businesses to thrive in the modern technological era. We observed a positive correlation between such optimization and enhanced Profitability and the ability to maintain sustainable operations, even in the face of industry disruptions. The discussion section delved into the nuanced interpretations of the results, emphasizing the critical role of human capital in adapting to technological changes and steering companies toward financial success and long-term sustainability. This understanding has significant implications for businesses aiming to navigate the challenges of the digital age while maintaining their commitment to sustainability. In conclusion, this study underscores the importance of strategically optimizing human resources in the context of technological advancements for both Profitability and sustainability in Indonesian businesses. It provides valuable insights for business leaders and policymakers seeking to develop strategies that align with the demands of the modern business landscape.